The validation case on invasive crustaceans of the LifeWatch ERIC Internal Joint Initiative: State of the art and next steps forward - Di Muri, Cristina; Arvanitidis, Christos; Basset, Alberto; De Giorgi, Raffaele; Rosati, Ilaria; Vaira, Lucia; Mancinelli, Giorgio (Frontiers in Environmental Science, 2023)
LifeWatch ERIC, the e-Science European infrastructure for biodiversity and ecosystem research, launched an internal joint initiative on Non-indigenous Species and Invasive Alien Species (NIS-IAS) as they are considered one of the major drivers of biodiversity and ecosystem change. Here, the case study focused on the trophic biogeography of invasive crustaceans is presented, describing the procedures, resources, and analytical web services implemented to investigate the trophic habits of these taxa by using carbon and nitrogen stable isotope data. The case study offers a number of analytical tools to determine the variability of the trophic position of invasive crustaceans in a spatially-explicit context and to model it as a function of relevant environmental predictors. Literature-based stable isotope data of the Atlantic blue crab Callinectes sapidus and of the Louisiana crayfish Procambarus clarkii have been used to evaluate the functionalities and outcomes of the workflow. The Tesseract Virtual Research Environment integrates all the analytical services offered by LifeWatch ERIC, including the ones developed for this case study, by means of a user-friendly interface. The analytical functions implemented for the crustacean workflow provide a proof of concept for future open e-science platforms focusing on NIS-IAS. The workflow conceptual structure can be adapted to a wide range of species, and can be further improved to support researchers in monitoring and predicting trophic-related impacts of NIS-IAS. In addition, it can support policy makers and stakeholders in the implementation of effective management and control measures to limit the negative effects of bioinvaders in recipient environments.